A colorimetric Boolean INHIBIT logic gate for the determination of sulfide based on citrate-capped gold nanoparticles1. Issue 72 (6th August 2015) - Deng, Hao-Hua; Wu, Gang-Wei; Lin, Xiao-Qing; Xu, Xiong-Wei; Liu, Ai-Lin; Xia, Xing-Hua; Chen, Wei
<x xml:space="preserve">Abstract</x> An INHIBIT logic gate is designed based on citrate-capped gold nanoparticles and successfully utilized to the determination of sulfide.